Bank Competition and Information Production - De Marco, Filippo; Petriconi, Silvio (Journal of Financial and Quantitative Analysis, 2024)
Abstract We show that bank competition diminishes banks’ incentives to produce information about prospective borrowers. We exploit the deregulation of U.S. interstate branching as a shock to competition and use borrowers’ stock returns after loan announcements to measure bank information production. Positive loan announcement returns are reduced in states that deregulate interstate branching, especially for opaque and bank-dependent firms and smaller banks that rely on soft information. Existing (i.e., inside) banks reduce information production more than new (i.e., outside) banks after deregulation, suggesting that they do so to deter borrower poaching. Furthermore, the probability of a covenant violation increases following deregulation.